2011
DOI: 10.1074/jbc.m110.209452
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Targets Aminoacyl-tRNA Synthetases to Translating Ribosomes

Abstract: Here, we examine tRNA-aminoacyl synthetase (ARS) localization in protein synthesis. Proteomics reveals that ten of the twenty cytosolic ARSs associate with ribosomes in sucrose gradients: phenylalanyl-RS (FRS), and the 9 ARSs that form the multi-ARS complex (MSC). Using the ribopuromycylation method (RPM) for localizing intracellular translation, we show that FRS and the MSC, and to a lesser extent other ARSs, localize to translating ribosomes, most strikingly when translation is restricted to poxvirus or alph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
94
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 50 publications
1
94
0
Order By: Relevance
“…[17,100,101] Previous studies have suggested a link between the tRNA aminoacylation and highmolecular-weight cellular complexes such as the cytoskeleton or ribosomes. [102][103][104] In all three domains of life, aaRSs form a variety of complexes with each other and with the non-enzymatic factors, [17,100] which may promote association of aaRSs with the ribosome. [102][103][104] However, the structural basis of these interactions and potential mechanistic implications are not well understood.…”
Section: Partic Ipation Of Serrs In Trna Recycling and Optim Iza Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,100,101] Previous studies have suggested a link between the tRNA aminoacylation and highmolecular-weight cellular complexes such as the cytoskeleton or ribosomes. [102][103][104] In all three domains of life, aaRSs form a variety of complexes with each other and with the non-enzymatic factors, [17,100] which may promote association of aaRSs with the ribosome. [102][103][104] However, the structural basis of these interactions and potential mechanistic implications are not well understood.…”
Section: Partic Ipation Of Serrs In Trna Recycling and Optim Iza Tionmentioning
confidence: 99%
“…[102][103][104] In all three domains of life, aaRSs form a variety of complexes with each other and with the non-enzymatic factors, [17,100] which may promote association of aaRSs with the ribosome. [102][103][104] However, the structural basis of these interactions and potential mechanistic implications are not well understood. Bacterial-type SerRS rarely interacts with other proteins and only a few interacting partners have been identified to date.…”
Section: Partic Ipation Of Serrs In Trna Recycling and Optim Iza Tionmentioning
confidence: 99%
“…Once formed on the ribosome, a puromycin conjugate dissociates from it and is free to diffuse rapidly, just like a completed polypeptide chain. The letter by Goodman et al (5) cites the work by David et al (6) as evidence that polypeptide-puromycin conjugates colocalize with ribosomes on the endoplasmic reticulum. This reading of the work by David et al (6) ignores the critical fact that the experiment was performed in the presence of cycloheximide (6), which blocks the dissociation of polypeptide-puromycin conjugates from ribosomes.…”
mentioning
confidence: 99%
“…The letter by Goodman et al (5) cites the work by David et al (6) as evidence that polypeptide-puromycin conjugates colocalize with ribosomes on the endoplasmic reticulum. This reading of the work by David et al (6) ignores the critical fact that the experiment was performed in the presence of cycloheximide (6), which blocks the dissociation of polypeptide-puromycin conjugates from ribosomes. Furthermore, the work by David et al (6) used a permeabilization step before fixation to remove soluble polypeptide-puromycin conjugates (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation